Identification of nitric oxide-releasing derivatives of oleanolic acid as potential anti-colon cancer agents1. Issue 25 (21st March 2015) - Fu, Junjie; Zou, Yu; Huang, Zhangjian; Yan, Chang; Zhou, Qimeng; Zhang, Huibin; Lai, Yisheng; Peng, Sixun; Zhang, Yihua
<x xml:space="preserve">Abstract</x> NO-releasing hybrid 6 regulates colon cancer-related signaling pathways, exhibiting potent anti-colon cancer activity in vitro and in vivo.